The Semaglutide: A revolution in the treatment of obesity and prevention of cardiovascular disease - Wiktoria Bilska; Ada Żydek; Urszula Ciułek; Wiktoria Paduch-Jakubczyk; Michalina Dubińska; Wiktoria Zduńczyk; Anna Dobosz (Quality in Sport, 2024)
Introduction and Objective: Obesity represents a significant public health concern in the 21st century, with a substantial burden of disease attributable to its complications, including type 2 diabetes, hypertension, and cardiovascular disease. The objective of this review is to evaluate the efficacy and safety of semaglutide, a GLP-1 receptor agonist, in the treatment of obesity and its impact on cardiometabolic risk factors.